Overexpression of the translocon accessory protein YajC alleviates toxicity of the endogenous pore-forming toxin LdrA in Escherichia coli - Yuto Nakamura; Yoshihiro Yamaguchi (PLoS ONE, 2025)
Almost all bacterial species possess toxin-antitoxin (TA) systems. In Escherichia coli , LdrA is a small membrane protein that functions as a pore-forming toxin. Expression of LdrA results in transient growth arrest, from which cells subsequently recover; however, the underlying recovery mechanism remained unknown. In the present study, we investigated the molecular basis for this recovery. Using a genetic screen, we identified YajC, an accessory protein of the SecDF-YajC translocon, as a key factor in counteracting of LdrA toxicity. We demonstrate that overexpression of YajC effectively alleviates LdrA toxicity without affecting its membrane localization or stability. This suppressive activity was specific for the Ldr toxin family, including LdrA and its homolog LdrD. Furthermore, our results indicate that YajC recognition of LdrA requires both its transmembrane and cytoplasmic domains. These findings reveal a novel function for YajC in counteracting a membrane-damaging toxin, distinct from its known role in the Sec-dependent protein translocation pathway.